2023
DOI: 10.3390/app13020813
|View full text |Cite
|
Sign up to set email alerts
|

Possible Locking Shock Time in 2–48 Hours

Abstract: An hourly scale precursor of inland earthquakes (EQs) is revealed in this paper. Several EQ cases in China have been reported. As indicated by a table listing 23 inland EQs and their shock time, epicenter location, magnitude, near-epicenter weather conditions, precursor start time and precursor duration, when the weather conditions are fair near the epicenter, an anomalously negative atmospheric electrostatic signal is readily observable approximately 2–48 h before the EQ occurs. Moreover, a successful single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Additionally, the decay of radon radiation leads to a decrease in the atmospheric electric field, as demonstrated in Figure 2a,b. This observation coincides with the statistical results in Chen et al [74], which indicate that negative abnormal signals in the atmospheric electric field usually appear 2-48 h before major earthquakes. However, the periodic changes in atmospheric pressure, electromagnetic field, and TEC anomalies cannot be fully explained by the chemical channel alone.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the decay of radon radiation leads to a decrease in the atmospheric electric field, as demonstrated in Figure 2a,b. This observation coincides with the statistical results in Chen et al [74], which indicate that negative abnormal signals in the atmospheric electric field usually appear 2-48 h before major earthquakes. However, the periodic changes in atmospheric pressure, electromagnetic field, and TEC anomalies cannot be fully explained by the chemical channel alone.…”
Section: Discussionsupporting
confidence: 92%
“…He noticed that negative anomalies in atmospheric vertical static electric signals always appeared several hours or tens of hours before seismic ruptures of varying magnitudes. Subsequent investigations revealed that when spatial electric field anomalies occurred, a strong earthquake might occur within a range of 30 to 55 kilometers from the observation site within 2 to 48 hours (Chen et al, 2023) [1]. However, it is not feasible to infer earthquake magnitude, epicenter, or seismic occurrence time solely based on the signals from individual stations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, large amounts of positive and negative ions are produced in the atmosphere by radioactive matter originating from the crust. Finally, a unique polarized electric field can be formed in the atmosphere that can alter the direction of the formal background atmospheric vertical electric field [21], as shown in Figure 2. Four cases (the Beijing Ms 3.0, Rongxian Ms 4.7, Changning Ms 6.0, and Wenchuan Ms 8.0 EQs) of preseismic atmospheric electric field hourly scale anomalies are shown in Figure 2, and the time scales for the advancement of the atmospheric electrostatic anomalies are 3.8, 11, 23.5 and 7 h, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…alter the direction of the formal background atmospheric vertical electric field [21], as shown in Figure 2. Four cases (the Beijing Ms 3.0, Rongxian Ms 4.7, Changning Ms 6.0, and Wenchuan Ms 8.0 EQs) of preseismic atmospheric electric field hourly scale anomalies are shown in Figure 2, and the time scales for the advancement of the atmospheric electrostatic anomalies are 3.8, 11, 23.5 and 7 h, respectively.…”
Section: Introductionmentioning
confidence: 99%